Assessment of malaria parasitemia in people living with HIV/AIDS in Kumba, Cameroon - Eyong Clinton Achere; Adamu Ndongho Ndifontiayong; Fokunang Charles Ntungwen; Nsagha Dickson Shey (Open Journal of Tropical Medicine - Peertechz Publications, 2022)
Background: Malaria parasitemia and HIV infections are globally important public health concerns. People residing in regions where these two infections are endemic are prone to develop co-infection. Sub-Saharan Africa has the greatest burden of both diseases and Cameroon particularly the South West Region has been reported as one of the regions with the highest malaria and HIV prevalence. Hence, there is a need for continuous monitoring and epidemiologic inquiry to generate updated data on the burden of malaria parasitemia on HIV/AIDS. The aim of this study was to determine the prevalence of malaria parasitemia and the association between viral load and malaria parasite density in people living with HIV/AIDS in Kumba, Cameroon.  Methods: A cross-sectional study was conducted involving 250 people living with HIV/AIDS selected from five main Community Based Organizations in Kumba during a period of 5 months from April to August 2021. Participants' consent was obtained followed by socio-demographic and other useful data via a standardized questionnaire. Capillary blood samples were collected and Giemsa-stained blood films were examined to detect malaria parasitemia. The recent viral loads were collected from the participants' medical files. Pearson's chi-square was used for the comparison of proportions and correlation analysis to determine the association between parasite density and viral load. Statistical significance was set at p < 0.05. Results: An overall prevalence of malaria parasitemia in people living with HIV/AIDS in Kumba was 27.2%; [95% CI: 21.8% - 33.2%]. Among 215 participants who were HAART-experienced, 49(22.79%); [95% CI: 17.6% - 27.9%] were found to be positive for malaria parasitemia while 19(54.29%); [95% CI: 48.1% - 60.5%] out of the 35 HAART naïve individuals were positive for malaria parasitemia. This difference in prevalence was statistically significant (X2 = 15.078, df = 1, N = 250, p < 0.000). Also, malaria parasite density was significantly dependent on viral load (X2 = 61.065, df = 6, N = 49, p < 0.000). HAART-experienced participants with high viral load(>1000copies/ml) had significantly higher malaria parasite density(>400trophozoites/µL) than HAART-experienced participants with 'not detectable' viral load.  Conclusion: The prevalence of malaria parasitemia in the study population was 27.2%. HAART naïve individuals had significantly higher malaria parasitemia prevalence and malaria parasite density than HAART-experienced individuals. Malaria parasite density was significantly dependent on viral load in HAART-experienced individuals.